Penerapan Metode Analytical Hierarchy Process (AHP) dan Simple Additive Weighting (SAW) dalam Pemilihan Tembakau Terbaik - Novica Irawati; Muhammad Yasin Simargolang; Yustria Handika Siregar; Evi Kurnia Wati (Universitas Asahan, 2021)
Abstract - Indonesia is one of the good tobacco producing countries. Tobacco is a plant that is grown by farmers and is a seasonal agricultural product that functions as a material to fill one's spare time or commonly referred to as raw material for cigarettes and cigars. In addition, the function of tobacco is also as a medical raw material (drugs, and tobacco can also be chewed. From the known function of tobacco leaves. Therefore, there is a need for requirements in selecting the best termbakau leaves based on the criteria determined by the tobacco production company, namely elasticity. , light color, aroma, sorting, price. Therefore, the researcher built a decision support system for selecting the best tobacco leaf which later aims to make it easier for farmers to choose which leaves are suitable or not for production. This research uses two methods, namely the method Analytica Hierarchyl Process (AHP) to determine eigenvalues as well as consistency and Simple Additive Weighting (SAW) to determine the suitability rating and also the ranking results. Keywords - Tobacco Leaves; AHP; SAW Abstrak - Negara Indonesia adalah salah satu negara penghasil tembakau yang baik. Tembakau adalah sebuah tanaman yang di ditanam oleh petani dan sifatnya produk pertanian musiman yang berfungsi sebagai bahan mengisi waktu luang seseorang atau biasa disebut dengan bahan baku rokok dan juga cerutu. Selain itu fungsi tembakau juga sebagai bahan baku medis (obat-obatan, dan juga tembakau dapat di kunyah. Dari fungsi daun tembakau yang telah diketahui. Maka diperlukan nya persyaratan dalam pemilihan daun termbakau yang baik berdasarkan kriteria yang sudah ditentukan oleh perusahaan produksi tembakau yaitu elastisitas, warna terang, aroma, sortasi, daya bakar (tahan lama). Oleh karena itu, peneliti membangun suatu sistem pendukung keputusan pemilihan daun tembakau terbaik yang nantinya bertujuan untuk memudahkan para petani memilih manakah daun yang layak atau tidak nya untuk di produksi. Penelitian ini menggunakan dua metode yaitu metode Analytica Hierarchyl Process (AHP) untuk menentukan nilai eigen dan juga konsisten dan Simple Additive Weighting (SAW) menentukan rating kecocokan dan juga hasil perangkingan.Kata Kunci - Daun Tembakau; AHP; SAW